Виділення детермінованої складової періодично нестаціонарних випадкових процесів методом найменших квадратів - Яворський, І.М.; Юзефович, Р.М.; Кравець, І.Б. (Фізико-механічний інститут ім. Г.В. Карпенка НАН України, 2010)
The investigation results of mean least square estimate for periodically nonstationary processes – mathematical model of stochastic oscillations – are considered. The formulas for estimate statistical characteristics are analyzed. The examples of typical processes analysis are shown.